Association between Number of Prior Cesareans and Early Preterm Delivery in Women with Abnormal Placentation - Oben, Ayamo; Ausbeck, Elizabeth B.; Gazi, Melissa N.; Subramaniam, Akila; Harper, Lorie M.; Szychowski, Jeff M.; Tita, Alan T. (American Journal of Perinatology, 2020)
Objective Delivery timing at 34 to 36 weeks is nationally recommended for pregnancies complicated by placenta accreta spectrum (PAS). However, it has recently been suggested that those with ≥2 prior cesarean deliveries (CD) and PAS should be delivered earlier than 34 weeks because of a higher risk of unscheduled delivery and complications. We sought to evaluate whether the number of prior CD in women with PAS is associated with early preterm delivery (PTD) (<34 weeks). We also evaluated the same relationship in women with placenta previa alone (without PAS).Study Design This is a secondary analysis of a multicenter and observational study that included women with prior CD (maternal–fetal medicine unit cesarean registry). Women with a diagnosis of PAS (regardless of placenta previa) were included for our primary analysis, and women with known placenta previa (without a component of PAS) were independently analyzed in a second analysis. Two groups of patients from the registry were studied: patients with PAS (regardless of placenta previa) and patients with placenta previa without PAS. The exposure of interest was the number of prior CD: ≥2 CD compared with <2 CD. The primary outcome was PTD <34 weeks. Secondary outcomes included preterm labor requiring hospitalization or tocolysis, transfusion of blood products, composites of maternal and neonatal morbidities, and NICU admission. Outcomes by prior CD number groups were compared in both cohorts. Backward selection was used to identify parsimonious logistic regression models.Results There were 194 women with PAS, 97 (50%) of whom had <2 prior CD and 97 (50%) of whom had ≥2 prior CD. The rate of PTD <34 weeks in women with ≥2 prior CD compared with <2 in the setting of PAS was 23.7 versus 29.9%, p = 0.27; preterm labor requiring hospitalization was 24.7 versus 13.5%; p = 0.05. The rates of plasma transfusion were increased with ≥2 prior CD (29.9 vs. 17.5%, p = 0.04), but there were no differences in transfusion of other products or in composite maternal or neonatal morbidities. After multivariable adjustments, having ≥2 CDs was not associated with PTD <34 weeks in women with PAS (adjusted odds ratio (aOR): 0.73, 95% confidence interval [CI]: 0.39–13.8) despite an association with preterm labor requiring hospitalization (aOR: 2.69; 95% CI: 1.15–6.32). In our second analysis, there were 687 women with placenta previa, 633 (92%) with <2 prior CD, and 54 (8%) with ≥2 prior CD. The rate of PTD <34 weeks with ≥2 CD in the setting of placenta previa was not significantly increased (27.8 vs. 22.1%, aOR: 1.49; 95% CI: 0.77–2.90, p = 0.08); the maternal composite outcome (aOR: 4.85; 95% CI: 2.43–9.67) and transfusion of blood products (aOR: 6.41; 95% CI: 2.30–17.82) were noted to be higher in the group with ≥2 prior CD.Conclusion Women with PAS who have had ≥2 prior CD as compared with women with <2 prior CD did not appear to have a higher risk of complications leading to delivery prior to 34 weeks. As such, considering the associated morbidity with early preterm birth, we would not recommend scheduled delivery prior to 34 weeks in this population.Key Points
Keywords: morbidly adherent placenta; placenta accreta; placenta previa